A critical examination of the coherence-based genealogical method in New Testament textual criticism - Gurry, Peter J. (New Testament Tools, Studies and Documents, 2017)
This study offers the first sustained examination of the Coherence-Based Genealogical Method (CBGM), a computerized method being used to edit the most widely-used editions of the Greek New Testament. Part one addresses the CBGM's history and reception before providing a fresh statement of its principles and procedures. Parts two and three consider the method's ability to recover the initial text and to delineate its history. A new portion of the global stemma is presented for the first time and important conclusions are drawn about the nature of the initial text, scribal habits, and the origins of the Byzantine text. A final chapter suggests improvements and highlights limitations. Overall, the CBGM is positively assessed but not without important criticisms and cautions.